Paolo Caccia Dominioni’s work for the Italian embassy at Ankara - Cristina Pallini; Armando Scaramuzzi (ABE Journal, 2018)
Based on research carried out at the Caccia Dominioni family archive, this contribution tells the intriguing story of the Italian Embassy at Ankara (1938-1940), a project involving Paolo Vietti Violi (1882-1965), Florestano di Fausto (1890-1965) and Paolo Caccia Dominioni (1896-1992). The main point of our paper is assessing Caccia Dominioni’s role, from a construction manager to the author of a “variant” which actually introduced a completely new layout. He was working at the site from April 1938 to 1940, running day-to-day operations, taking care of the financial management, hiring and looking after workers, maintaining official relations with Italian and Turkish authorities, supervising the supply of materials, and developing Di Fausto’s drawings, which arrived rarely and mostly incomplete. Caccia Dominioni’s “variant” introduced a completely new layout, resulting from a thorough understanding of the landscape potential, fully exploiting the opportunities provided by the diagonally sloping ground. Rather than a single group of monumental buildings, Caccia Dominioni envisaged a variety of structures, each dedicated to a specific function, sized and shaped accordingly. Altogether, the Embassy looked like a village, a “city within a city” so common for foreign legations in the Levant.